Description of a new species, Toxorhynchites (Toxorhynchites) tyagii (Diptera: Culicidae), from Nilgiri hills, Western Ghats, southern India - Krishnamoorthy, R.; Munirathinam, A.; Dhananjeyan, K. J.; Hiriyan, J.; Mariappan, T.; Samuel, P. Philip; Venkatesh, A. (Zootaxa, 2013)
Specimens of Toxorhynchites (Toxorhynchites) tyagii, sp. n., were collected from the fringe areas of Gudaloor town, Ooty in the Nilgiri hills at an altitude of 1000 m above sea level in Western Ghats ranges in southern India during October 2011and from Darjeeling ranges in the northern hilly region of Raymatang TG in Jalpaiguri district, West Bengal, in eastern India during February 2012. The adults, pupa and fourth-instar larva of this species are described and illustrated to distinguish it from Toxorhynchites (Tox.) splendens and Toxorhynchites (Tox.) edwardsi, which are the closest allies of Tx. (Tox.) tyagii. Besides possessing remarkable distinguishing male genital characteristics, Tx. tyagii differs from Tx. splendens also by the presence of conspicuous yellow scale-patches over the wing root that extend to the scutellum, and differs from Tx. edwardsi by having midtarsomeres 3–5 all dark whereas in Tx. edwardsi tarsomeres 3 and 4 and a larger part of 5 are white.